PENANAMAN NILAI-NILAI AL-QURAN KEPADA PESERTA DIDIK SEBAGAI WUJUD PENDIDIKAN KARAKTER DI SMP NEGERI 3 PURWAKARTA - Lusiana, Lisa (Program Studi Pendidikan Agama Islam, Fakultas Agama Islam Universitas Islam Malang, 2022)
Human resources that have superior quality in terms of character are one of the main assets in building a nation. To produce this generation, schools play an important role in providing character provisions for students. One of the efforts that can be done is through the application of character education. The application of character education in schools can be realized in various ways, one of which is by inculcating the values of the Qur'an. This research was conducted at SMP Negeri 3 Purwakarta which aims to see how the implementation of the cultivation of Al-Quran values as a form of character education. In conducting this research, the researcher used a qualitative descriptive method with data collection techniques through interviews. The results showed that the cultivation of the values of the Koran as a form of character education was implemented through several programs including; The implementation of the dhuha prayer, the reading of Tadarus and the Koran and finally the cultivation of character. Educators in collaboration with stakeholders continue to synergize to implement character education even though there are various obstacles in its implementation.Keywords : Al-Quran Values, Students, Character Education